WORLD’S URBAN SUSTAINABLE POLICIES AND SUSTAINABILITY IN ALGERIA - SAOUDI, HADJIRA; BELAKEHAL, AZEDDINE (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
Although the political structure of Algeria is quite different from western countries, and although Algeria’s budget is mainly from oil revenues and thus is not sustainable as western countries, all countries shared relatively common failures regarding environmental sustainability. This paper argues that failure to achieve sustainability will continue in all countries because of similarities of several phenomena regardless of political diversity. Phenomena such as: 1) the ambiguity of defining environmental, economic and social sustainability; 2) the impossibility of having the power or the means to implement agreements, rules or regulations to achieve sustainable environments; 3) the equilibrium between development and sustainability is not yet found economically; 4) conflict of interests between generations on the one hand, and between developed and less develop countries on the other, were never solved except in written formats or agreements that were not often applied. Thus, all attempts to achieve sustainability will remain tacit unrealized potentials within current political structures.